Understanding the Relationship Between Refugees and the Host Community Through Afghan Refugees’ Lived Experiences in Pakistan - Malik, Beenish (Animo Repository, 2020)
With massive forced displacement, hosting refugees has become one of the leading concerns for developing countries like Pakistan. In the given context, this article is an attempt to unfold the nature of the relationship between the Afghan refugees and their Punjabi host community. To understand, describe, and interpret the essence of the refugees’ lived experiences, 31 adult Afghan refugee scavengers were involved in this qualitative study through semi-structured in-depth interviews. The collected data revealed that while being in exile, the Afghans had formed new relationships with their hosts. These relationships were generally positive and reciprocal in nature. The Afghans confirmed the absence of discrimination and harassment from the hosts and highlighted both the monetary and nonmonetary help that they receive from the native residents at times. However, despite being in good terms, Afghan refugees reported restricted movements with the host community. The reasons were predominantly grounded in Afghan traditions of protecting the honor of the women and the privacy of the household by limiting the contact with native residents. It emphasizes the need to further enhance the interaction among refugees and hosts.